What do I do? Developing a competency inventory for postgraduate (residency) program directors. (2nd October 2016) - Lieff, Susan J.; Zaretsky, Ari; Bandiera, Glen; Imrie, Kevin; Spadafora, Salvatore; Glover Takahashi, Susan
Abstract: Background : Few new Residency Program Directors (PD) are formally trained for the demands and responsibilities of the leadership aspect of their role. Currently, there are no comprehensive frameworks that describe specific leadership competencies that can inform PD self-reflection or faculty development. Methods : The authors developed a Postgraduate Program Director Competency Inventory (PPDCI) in order to frame the performance of PDs for a multisource feedback (MSF) program. The development of the PPDCI occurred in five phases which involved: development of an initial inventory, implementation of a key informant survey of national opinion leaders, execution of a validity survey with postgraduate education leaders and committee members and implementation of a further refined inventory with 17 PD and 147 raters as part of a pilot MSF program. Outcomes : Five distinct domains of leadership competence were identified which included: Communication and relationship management, leadership, professionalism and self-management, environmental engagement, and management skills and knowledge. The content validity of the PPDCI was endorsed by 85% of the key informants. The validity survey indicated strong endorsement of the PPDCI domains and recognition of its utility for both orientation of new PD as well as a frame for self-assessment. The pilot MSF program yielded a further refined and reduced inventory of 26 items of competence as well as recommendations for its utility. Conclusions : Use of this leadership inventory has the potential to ensure effective leadership of postgraduate programs.